Use of Mica Mineral Powder in Bricks Industry to Improve the Performances - Mostaghelchi, M.; Zahiri, R.; Miremad, S.H.; Ebadi, A.G. (Asian Journal of Chemistry, 2013)
In this work, the usability of mica mineral powder as an additive material in industrial brick were investigated. Mica mineral was acquired from an inactive mica mine which is located at the south of Shahrod, Semnan, Iran and industrial brick mortar was obtained from a brick company in Damghan. Mica mineral and brick mortar were prepared for various processes of industrial brick investigation. Mica mineral were powdered and this powder in different proportions was mixed with industrial brick mortar, starting amount of 0 wt % up to 15 wt % in 54-10 mm bar shape. Bars for testing of physico-mechanical properties of the samples having different mica mineral powder composition. These prepared bars were uniaxially pressed and sintered at the 1100 ºC during 1 h. It was found that the amount of mica mineral additive had positive effect on the physical, chemical and mechanical strength of the produced industrial brick. With increasing demands of the construction industry, bricks quality and cost become more important day by day in Iran. In addition, the usage of mica mineral powder for the production of industrial bricks has significant important role on reacting the local mica mine and local jobs for populace along with a great contributions to economy and ecology of the country. In this study, the efficiency of mica powder additives to produce better bricks was suggested.